2008
DOI: 10.1590/s0102-311x2008000300022
|View full text |Cite
|
Sign up to set email alerts
|

Fórum: racionamento dos cuidados de saúde. Introdução

Abstract: Explicit rationing of health care is one of the most important issues under debate in the academic and political fields in both developed and developing countries. The articles presented in this Forum provide an approach to some of the questions relating to this issue. The approach is multidisciplinary, covering complex ethical questions and the contribution of economics to the debate. The analyses reveal specificities associated with the shift from implicit approach for rationing of health care, traditionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Similarly, in Brazil, neither random citizens 14 nor Brazilian bioethicists 15 can agree on what constitutes reasonable allocation of healthcare resources. Nevertheless, building upon the forum for the rationing of healthcare services 1 , we argue that the explicit rationing of healthcare resources, both in the public and Supplementary systems, must occur in order to enable societal education and legitimate participation in the shaping of modern societal values in Brazil regarding the financing and delivery of healthcare services.…”
Section: Principles For Rationing Healthcare Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Brazil, neither random citizens 14 nor Brazilian bioethicists 15 can agree on what constitutes reasonable allocation of healthcare resources. Nevertheless, building upon the forum for the rationing of healthcare services 1 , we argue that the explicit rationing of healthcare resources, both in the public and Supplementary systems, must occur in order to enable societal education and legitimate participation in the shaping of modern societal values in Brazil regarding the financing and delivery of healthcare services.…”
Section: Principles For Rationing Healthcare Resourcesmentioning
confidence: 99%
“…Three years ago, the forum on the rationing of health services 1 provided an excellent starting point for discussing means of distributing healthcare resources more reasonablywithin Brazil. Recently, an overview of the Brazilian healthcare system concluded that the most sizeable barrier to securing the right of healthcare for every Brazilian is, in fact, political 2 .…”
mentioning
confidence: 99%
“…Essas diferentes bases de acesso consideradas apenas se justificam porque no mercado da saúde não existe preço para regular a oferta e a procura, agravado pelo fenômeno da procura induzida pela oferta, surgindo então a necessidade de priorizar e/ou racionar porque a procura de cuidados de saúde não condicionada pelo preço enfrenta uma oferta de cuidados de saúde condicionada por considerações de custos. Sob estas condições a procura pelos serviços de saúde suplantará sempre a sua oferta 3 . Neste âmbito, podemos definir priorização dos cuidados como escolhas hierarquizadas entre alternativas de cuidados disponíveis, dentro dos limites de recursos do sistema 4 , e racionamento como uma política implícita ou explicita que restringe medidas específicas de cuidados de saúde, fundamentada pelo fato de que os custos são proibitivos para o sistema de saúde e a sociedade 4 .…”
unclassified
“…O sucesso de uma política de priorização dos cuidados de saúde depende da incorporação dos valores e aspectos culturais da sociedade a que respeita. (PINHO, 2008) O SUS tem uma clientela potencial de quase 200 milhões de pessoas, já que nossa Conceitos contábeis como gastos, investimentos, custos e despesas são diferenciados como: a) Gastostodas as ocorrências de pagamentos de ativos, custos ou despesas, de grande abrangência e generalização; b) Investimentosaplicação de recursos em ativos ou despesas e custos que serão imobilizados ou diferidos, cria um benefício futuro; c) Custossão gastos necessários à fabricação de produtos (no âmbito do SUS os produtos são serviços prestados) e d) Despesasde modo geral, são ligados à áreas administrativas, gastos necessários para vender e enviar produtos. (PADOVEZE, 2010) Albuquerque, Medeiros e Feijó (2008) afirmam que despesa pública é toda utilização de recursos públicos no custeio das atividades, manutenção de instalações e equipamentos, prestação de serviços ou ainda realização de investimentos e outros gastos.…”
Section: Sistema úNico De Saúdeunclassified